Draft Five Year Plan 1978-83 Loans to Government Servants Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
The policy of the State Government is to encourage House Building by Government Servants. This Policy term. to reduce the liability of the State Government to construct residential houses for them. As such expenditure on grant of loans to Government Servants for this purpose is increasing every year. Since 1976-77 demand for the advance has gone up nearly 3 times partly due to expansion in house building activities of the M.P. Housing Board, development of Private housing Colonies throughout the State and partly due to rise in house rents of private houses in urban area and increase in quantum of advance by Government due to rise in cost of plots and construction of houses. the procedure for obtaining the advance has also been simplified and the condition of putting in completed years of service has also been reduced to 12 years from 15 years. This has also created demand for the advance.
Government of Madhya Pradesh, Planning, Economics and Statistics Department